Use of an aerodynamic wake emulator to assess the impact on a high-performance ground vehicle in close proximity - Cardona, Jordi; Proenca, Anderson R.; Garry, Kevin P. (American Institute of Aeronautics and Astronautics (AIAA), 2023)
The interaction between ground vehicles in close proximity is currently of interest as it is known that the aerodynamic characteristics of the trailing vehicle may change significantly under the effect of a disturbed flow. The aim of this work is to map a wide range of situations where a trailing car, under racing conditions, is affected by another vehicle ahead. A sub-scale wind tunnel test in which the aerodynamic characteristics of a high-performance ground vehicle is affected by a simplified ‘wake emulator’ has been conducted. The trailing vehicle is a 35% scale model of the generic DrivAer geometry. These experiments were carried out at Cranfield University’s 8x6 Wind Tunnel facility, at a speed of 40 m/s. Several relative positions, such as longitudinal and lateral distances, together with different yaw angles have been investigated. The behavior of the trailing car is monitored with an internal balance that gathers the variations of all aerodynamic forces. Thus, a well detailed map displays the effect of close slipstreaming in high-performance cars alongside the variations due to yaw conditions. Results have shown similar trends on axial and vertical force as previous works regarding high performance vehicles. The variation on aerodynamic forces and moments are highly dependent on the relative position with the main vortices from the leading car’s wake.